PERSEPSI MASYARAKAT KOTA SITUBONDO TERHADAP PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) - Pramitasari, Triska Dewi (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
This study aims to determine the perceptions of the people of Situbondo City on the use of financial technology (Fintech). The technique of collecting data uses an in-depth interview method to 10 informants with different ages and professions. Data analysis techniques use qualitative descriptive methods. The results of the study explained the public perception of the use of fintech which included attitudes, understanding, interests, motivations, and expectations. The attitude of the community towards the use of fintech is open and continues to support financial technology innovation in Indonesia. Although people do not really understand the benefits and use of fintech properly, but in terms of community interest in using fintech, it can be seen from the results of interviews where 7 respondents were interested in using it. Therefore, the community hopes for fintech organizers to be more frequent in providing socialization to the community and the ease of using services, so that people who do not understand technology can use it more easily.